Bibliometric Analysis of Religious Education Systems in Schools: Trends, Themes, and Future Directions - Latifatul Inayati, Nurul; Rohmani, Annas Fajar (Universitas Muhammadiyah Surakarta, 2025)
This study conducts a bibliometric analysis of research on